Effects of dietary cholesterol on hepatopancreas associated with morphotypic differentiation in male Amazon River Prawns, Macrobrachium amazonicum (Heller, 1862) - Ruiz, Thalles Fernando Rocha [UNESP]; Ribeiro, Karina; Vicentini, Carlos Alberto [UNESP]; Vicentini, Irene Bastos Franceschini [UNESP]; Papa, Luciene Patrici (Hindawi, 2019)
Cholesterol is a necessary element in the diet of prawns and it is involved in the metabolic processes of sexual maturation and synthesis of the molting hormone. Freshwater prawns are not able to synthesise cholesterol from specialised metabolic pathways. The aim of this study was to describe changes in structural and morphometric patterns of hepatopancreas associated with morphotypic differentiation of males Macrobrachium amazonicum when fed with different levels of cholesterol. Considering the four morphotypes of this species, Translucent Claw morphotype specimens were split into experimental units and divided into four groups, fed with different levels of cholesterol (0%, 0.5%, 1%, 2%) for 50 days. They were collected as they reached Green Claw (GC) morphotype, weighed to determine the hepatosomatic index, and the hepatopancreas was processed in histological routine for morphologic and morphometric analysis. In this study, it was possible to observe that the 2% cholesterol treatment exhibited more animals that reached the GC morphotype, and there was no significant weight gain in all treatments. Histologically, B-cell abundance and hypervacuolized as well as F- and R-cells shortages were observed as the percentage of cholesterol increased. This alteration in cellular profile correlates with the morphometric analyses that exhibited an increase in epithelial area and alterations in the lumen shape. This imbalance observed in the lumen-epithelium relationship may be associated with a low digestive performance and possibly congested the functions of hepatopancreas. Thus, high doses of cholesterol promoted morphotypic differentiation without weight gain, due to alterations on hepatopancreas.
Keywords: B-cells; F-cells; morphometry; R-cell; vacuolization